VD_FINDINFO Jug / 2018 / 127 vom 20. Juli 2017 - VD Tribunal cantonal (2017)
HOMICIDE PAR NÉGLIGENCE, FIXATION DE LA PEINE, APPRÉCIATION DES PREUVES, PARTIE CIVILE | 41 CO, 117 CP, 47 CP, 27 LCR, 31 LCR, 10 CPP (CH), 126 CPP (CH)